Vertical-horizontal flow roughing filter for improving water quality in sustainable water supply infrastructure - Anggara Wiyono Wit Saputra; Prasetyo Rubiantoro; Very Dermawan (International Journal of Advances in Applied Sciences, 2026)
Water is fundamental to cooking, bathing and hygiene, and essentially for life itself. Across many areas, communities rely on bore well water as a source of raw water for domestic needs. Yet this resulting water is mostly not of an appropriate quality, as it has a high iron content and hardness. This study evaluates the performance of a combined vertical-flow and horizontal flow roughing filter (VRF and HRF) system for bore well water treatment. The system was tested using various alternative filter media, including coconut fiber, silica sand, activated carbon, zeolite, pumice stone, and volcanic black sand, arranged in different configurations. The vertical-flow unit used a media depth of 6 cm, while the horizontal-flow unit used a depth of 15 cm. The results showed that all configurations effectively improved water quality and met standard requirements. The highest performing model, consisting of volcanic black sand, activated carbon, zeolite, and silica sand, achieved a 97.5% reduction in iron and a 13.2% reduction in hardness. These findings indicate that optimized roughing filter systems offer a low cost and efficient solution for decentralized water treatment.